Maintenance Decision Support System in Small and Medium Industries: An Approach to New Optimization Model - Tahir, Zulkifli; M.A., Burhanuddin; Anton, S P (Journal of Computer Science and Network Security, 2008)
Machine downtime can be defined as a total amount of time the machine would normally be out of service from the moment it fails until the moment it is fully repaired and back to operate. Once a unit experiences a service downtime or downgrade, the covariates or risk factors can directly impact on the delay in repairing activities. Our study reveals the model to identify the potential risk factors that either delay or accelerate repair times, and it also demonstrates the extent of such delay, attributable to specific risk factors. Once risk factors are detected, the maintenance planners and maintenance supervisors are aware of the starting and finishing points for each repairing job due to their prior knowledge about the potential barriers and the facilitators.